Library Lil - Williams, Suzanne, 1949-; Kellogg, Steven (New York : Dial Books for Young Readers, 1997)
A formidable librarian makes readers not only out of the once resistant residents of her small town, but out of a tough-talking, television-watching motorcycle gang as well.
Keywords: Librarians -- Fiction; Books and reading -- Fiction; Reading -- Fiction; Tall tales